2017
DOI: 10.1159/000477937
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Cortex and Hippocampal γ-Secretase Activating Protein Levels in Prodromal Alzheimer Disease

Abstract: Background: β-Amyloid (Aβ) is the product of concerted cleavage of the amyloid precursor protein (APP) by β- and γ-secretases. However, the molecular mechanisms that regulate this process are not well understood. Recently, evidence was reported that γ-secretase activating protein (GSAP, 16 kDa), derived from a larger precursor protein (98 kDa), plays a role in Aβ metabolism through a mechanism involving its interaction with both γ-secretase and APP. However, a detailed evaluation of GSAP protein levels and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Our findings provide a route to the investigation of γ-secretase modulation and, ultimately, to the development of therapeutic agents for AD. In addition, abnormal activation of γ-secretase by GSAP that is associated with aging, AD, and Down syndrome (1416) may lead to AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide a route to the investigation of γ-secretase modulation and, ultimately, to the development of therapeutic agents for AD. In addition, abnormal activation of γ-secretase by GSAP that is associated with aging, AD, and Down syndrome (1416) may lead to AD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, GSAP RNAi mice crossed with double transgenic APPsweXPS1ΔE9 Alzheimer’s disease (AD) model mice have reduced Aβ burden (12), indicating that GSAP is a novel therapeutic target for the treatment of AD. Furthermore, genetic studies have shown that GSAP is linked with aging, AD, and Down syndrome (1416). Therefore, investigating the function of GSAP in Aβ production and in γ-secretase activity and specificity is critical for developing an in-depth understanding of γ-secretase modulation and effective AD therapeutics.…”
mentioning
confidence: 99%
“…Cells possess a different type of γ-secretase complexes with variable levels of activities (PDB structure: 6IDF), which under certain cellular circumstances GSMP can bind and modify its activity and selectivity (clockwise): endoplasmic reticulum (ER) stress upregulate stress-associated ER protein 1 (SERP1) expression which binds and localize the γ-secretase complex to lipid rafts where amyloid precursor protein (APP) resides thus increasing APP cleavage but not Notch processing (Jung et al, 2020), hypoxic conditions stabilize Hif-1α which in turn binds to γ-secretase and increase its activity for Notch substrates (Villa et al, 2014), innate immune response and aging triggers the binding of interferon-induced transmembrane protein 3 (IFITM3) thus enhancing γ-secretase for APP but reducing Notch processing (Hur et al, 2020) and under unknown conditions GSAP attenuates γ-secretase activity solely towards APP but not Notch (Wong et al, 2019; Magenta-Nicastrin, Green-Presenilin, Blue-Aph-1 and Red-Pen-2). GSAP that is associated with AD, which might associate GSAP as a disease-related risk factor (Zhu et al, 2014;Perez et al, 2017). This was the first study that demonstrated the extent to which GSMPs attenuate γ-secretase activity by interacting with the enzyme in the allosteric site and changing its active site conformation.…”
Section: γ-Secretase Activating Protein (Gsap)mentioning
confidence: 99%
“…A later study revealed that GSAP modulates γ-secretase activity by altering the active site and subsequently enhancing APP processing while not affecting Notch processing (Wong et al, 2019 ). In the case of GSAP, the precise cellular cue that is responsible for its interaction with γ-secretase is unclear, but there is an SNP in GSAP that is associated with AD, which might associate GSAP as a disease-related risk factor (Zhu et al, 2014 ; Perez et al, 2017 ). This was the first study that demonstrated the extent to which GSMPs attenuate γ-secretase activity by interacting with the enzyme in the allosteric site and changing its active site conformation.…”
Section: γ-Secretase Activating Protein (Gsap)mentioning
confidence: 99%
“…Nevertheless, GSAP RNAi mice crossed with double transgenic APPsweXPS1ΔE9 AD model mice have reduced Aβ burden 12 , indicating that GSAP is a novel therapeutic target for the treatment of AD. Furthermore, genetic studies have shown that GSAP is linked with aging, AD and Down syndrome [14][15][16] . Therefore, investigating the function of GSAP in Aβ production and γ-secretase activity and specificity is critical for developing an in-depth understanding of γ-secretase modulation and effective AD therapeutics.…”
Section: Introductionmentioning
confidence: 99%